Design and placement of synthetic sex pheromone traps for cacao mirids in Ghana. (17th January 2018) - Sarfo, J.E.; Campbell, C.A.M.; Hall, D.R.
Abstract: Cacao mirids ( Sahlbergella singularis, Distantiella theobroma and Bryocoropsis laticollis ) were captured in pheromone traps releasing a 2:1 blend of the sex pheromone components of the two first named species in a series of five experiments on cacao ( Theobroma cacao ) plantations in Ghana. A total of 835 cacao mirids were caught, all male, 95% of which were S. singularis, 3% D. theobroma and 2% B. laticollis. Two sticky trap and two water trap designs made from locally available materials were as effective for capturing S. singularis and total mirids as the best sticky trap from previously reported studies. Coating the outer surface of a large water trap with sticker increased the catch 4.4×, and 2.7× for a cylindrical sticky trap. Sticker on the outside of the water trap also increased the inside catch of S. singularis by 76% and total mirids by 71%. The numbers of S. singularis and D. theobroma trapped increased with increasing trap elevation and were highest around canopy level. Those traps caught an average 12× more mirids than traps at 1.8 m, the height recommended currently. Therefore, large water traps coated with sticker and aligned with the cacao canopy should raise the current capture rates of pheromone traps for cacao mirids about 50×, which may be sufficient for effective pest management by mass trapping without synthetic insecticides.